Trends and the need for new professions and forms of education in tourism and hotel management - Vujić, Vidoje; Bečić, Emira; Črnjar, Kristina (2008)
Tourism is a very significant sector of the economy in most countries. Its quality growth is not possible without an effective policy of developing human potential. All this, surely, is a weight to be borne in particular by hotel managers who are specifically responsible to ensure new know-how and professions within the corpus of employees. The paper shows the benchmarks and anticipates the prospects of tourism development. It deliberates over the modern forms of formal, not formal and informal education of personnel in tourism. It defines new trends in tourism and their impact on the professional development of personnel and on the innovating of knowledge to employees in tourism
Bibliografske bilješke uz tekst ; bibliografija: 20 jed
Keywords: Turizam -- Obrazovanje